Case Report: Toripalimab Combined With Anlotinib in a Patient With Metastatic Upper Tract Urothelial Carcinoma After Pembrolizumab Failure - Zan, Ning; Zhang, Xuan; Du, Lingyan; Lin, Zhiyu; Yu, Danfei; Liu, Juan; Gou, Fusheng (Frontiers in Oncology, 2022)
Urothelial carcinoma is the most common primary upper tract urinary carcinoma. If surgery, chemotherapy, and immunotherapy fail, the prognosis for upper tract urinary carcinoma is extremely poor. Immunotherapy combined with antiangiogenesis therapy is a new therapeutic regimen with a synergistic antitumor effect. We present a case of metastatic upper tract urinary carcinoma in which the patient underwent surgery and treatment with gemcitabine combined with platinum-based chemotherapy. Radiotherapy and second-line immunotherapy (pembrolizumab) were administered after the cancer had progressed to the left lymph node of the abdominal aorta in the umbilical plane. However, the patient developed liver metastases while being treated with pembrolizumab. He was administered off-label immunotherapy (toripalimab) combined with antiangiogenesis therapy (anlotinib) and achieved a long-term clinical response for over 25 months. Toripalimab combined with anlotinib has potential therapeutic value for locally advanced or metastatic upper tract urinary carcinoma in patients who had previously received platinum-based chemotherapy and had disease progression or after treatment with a PD-1 inhibitor.